A clinical decision rule to predict zygomatico-maxillary fractures. Issue 8 (August 2017) - Haworth, Simon; Bates, Anthony; Beech, Andrea; Knepil, Greg
Abstract: Patients presenting with periorbital trauma require clinical assessment to exclude zygomatico-maxillary fractures. A single-centre pilot investigation was undertaken at a general hospital in the United Kingdom. The sample was composed of 229 adult patients attending our emergency department with periorbital injuries. Findings from 17 signs or symptoms of facial injury were recorded on a validated tool. The relationship between clinical presentation and displaced zygomatico-maxillary fracture was assessed using diagnostic test parameters and tests for correlation. A decision-making rule was derived. The presence of a) palpable bony step, b) bony asymmetry, c) lateral sub-conjunctival haemorrhage with no posterior limit, d) anaesthesia or paraesthesia to lip/cheek or side of nose and e) palpable emphysema were all specific features of radiographically displaced zygomatico-maxillary fracture (specificity all >75.0 %, p value for correlation all <0.001). A decision-making rule based on the presence of any one of features (a), (c), (d) or (e) identified all patients with displaced zygomatico-maxillary fractures in this sample (sensitivity 100% (95% CI 93.4%–100.0%), specificity 72.6% (95% CI 65.3%–79.0%). Implementation of this clinical decision-making rule would identify all patients with displaced fractures at the triage stage whilst reducing radiographic exposures by 55% in this sample.